Treatment priorities among older people if faced with serious illness: improving the quality of life or extending life? - Jorge, Rafaela (2021)
Objective: This study aimed to analyse older people`s end-of-life care priorities and to identify factors associated with these priorities. Methods: A cross-sectional face-to-face survey with 400 individuals aged ≥60 living in the city of Belo Horizonte, Brazil was conducted. Participants were asked their treatment priorities if faced with a serious illness with limited time to live. Multinomial logistic regressions were used to identify the associated factors. The possible instability of the factors in the final multivariable model were assessed by bootstrap resampling. Results: Most participants (65.3%) chose the option ‘improve quality of life for the time they had left’. Only 4% said extending life was the most important priority while the option ‘both equally important’ (quality and extension) was chosen by 30.8 of respondents. Participants in the age group 60-69 years were more likely to choose both quality and life extension than choose to extend life alone (AOR=0.18, 95% CI:0.05-0.72; ref: 80+ years). The group comprised of single + widowers is more likely to prioritize both quality and extension than to prioritize just extending life (AOR=0.28, 95% CI:0.09- 0.89; ref: the others marital status) and or just improving the quality of life (AOR=0.62, 95% CI:0.40-0.95; ref: the others marital status). Conclusion: The findings indicated that treatment for improving the quality of life was the most important priority. Two factors influenced the priorities (age group and marital status). To meet people's treatment priorities at end of life, policies need to be formulated to develop palliative care services, train health-care professionals, and educate patients